Effect of Contextual Teaching and Learning Approach on Tenth Graders’ Writing Skills - Rahma, Aulia; Darmawan; Lebagi, Desrin; Marhum, Mochtar (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The objective of this research is to examine the effectiveness of contextual teaching and learning (CTL) approach to improve writing skill of the tenth grade students at MAN Insan Cendekia Kota Palu. The research employs pre- experimental research design. The population of this research is Grade X students at MAN Insan Cendekia Kota Palu, and the sample is Grade X Al-Qolam, consisting of 20 students. The researcher employs purposive sampling technique and takes one-group pre-test and post-test. The pre-test is administered to assess the student’s writing ability through the CTL Approach and to determine whether the class is equal or not in terms of their writing achievement before the treatment is given, and the post-test is used to administer students’ writing skill achievement after receiving the treatment. The result of the data analysis indicates that there is a significant difference in the students’ achievement in pre-test and post-test. It shows that the mean score of pre-test is ( 60.59) and the mean score of post-test is (76.33). The sig value (Asymp. 2-tailed) is 0.000, which is smaller than the p-value = 0.05, indicating that the alternative hypothesis (Ha) is accepted. Thus, the contextual teaching and learning approach is effective in improving the writing skill of grade X students at MAN Insan Cendekia Kota Palu.